PERAN BRAND AWARENESS MEMEDIASI PENGARUH AUGMENTED REALITY (AR) TERHADAP KEPUTUSAN PEMBELIAN - Nugraha Artha, I Putu Deva; Ekawati, Ni Wayan (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.12.NO.09.TAHUN.2023DO - 10.24843/EEB.2023.v12.i09.p20, 2023)
This study aims to analyze the role of brand awareness in mediating the effect of augmented reality (AR) on purchasing decisions. This research was conducted on the clothing brand Slashrock Gear in the city of Denpasar. Based on the responses from respondents to questionnaires distributed online to the people of Denpasar city who follow the Slashrock Gear brand Instagram social media account, the results show that in general augmented reality has not influenced purchasing decisions optimally. This study used a sample of 100 respondents, with a non-probability sampling method. Data collection was obtained from the results of distributing questionnaires online. The analytical technique used in this research is descriptive Statistikal analysis, classical assumption test, path analysis and Sobel test. The results of this study indicate that augmented reality (AR) has a positive and significant effect on purchasing decisions. Augmented reality (AR) has a positive and significant effect on brand awareness. Brand awareness has a positive and significant effect on purchasing decisions. Brand awareness has a positive and significant effect in mediating the effect of augmented reality (AR) on purchasing decisions